PROFIT ANALYSIS AS A COMPANY PERFORMANCE INDICATOR IN THE PERSPECTIVE OF IBNU KHOLDUN'S COMPANY THEORY - Adinata, Uslan; Wahidah, Sofiatul; Suib, Mohammad Syaiful (Universitas Nurul Jadid, 2025)
The aim of this research is to influence the company as an indicator in using Ibn Khaldun's theory. The research method used is a qualitative qualitative method to describe and make it easier for researchers with data collection techniques, observations, comments and literature studies. The research results show that Ibnu Khaldun is not only profit-oriented towards material benefits but also has non-material aspects such as piety, patience and gratitude.